Financial instruments of the banking sector of the Ukrainian economy in the context of international integration - Kobielieva, T. O.; Moroz, Karina (Національний технічний університет "Харківський політехнічний інститут", 2025)
The results of the study indicate that today the banking sector and the economy of Ukraine as a whole are experiencing difficulties that have not been overcome before. The result of the actions of the Ukrainian authorities, which were aimed at preventing the current situation, but are being taken today as operational measures, is already visible.
Фінансові інструменти банківського сектору економіки України в контексті міжнародної інтеграції
Keywords: finance; banking sector; economics; international integration; enterprises